An integrated satellite–terrestrial 5G network and its use to demonstrate 5G use cases. (20th February 2021) - Evans, Barry; Wang, Ning; Rahulan, Yogaratnam; Kumar, Satish; Cahill, Joe; Kavanagh, Mark; Watts, Simon; Chau, Duy‐Kha; Begassat, Yann; Brunel, Alain‐Pierre; Masson, Thierry; Diarra, Mamoutou
Summary: In this paper, we present a satellite‐integrated 5G testbed that was produced for the EU‐commissioned Satellite and Terrestrial Networks for 5G (SaT5G) project. We first describe the testbed's 3GPP Rel. 15/6‐compliant mobile core and radio access network (RAN) that have been established at the University of Surrey. We then detail how satellite NTN UE and gateway components were integrated into the testbed using virtualization and software‐defined orchestration. The satellite element provides 5G backhaul, which in concert with the terrestrial/mobile segment of the testbed forms a fully integrated end‐to‐end (E2E) 5G network. This hybrid 5G network exercised and validated the four major use cases defined within the SaT5G project: cell backhaul, edge delivery of multimedia content, multicast and caching for media delivery and multilinking using satellite and terrestrial. In this document, we describe the MEC implementations developed to address each of the aforementioned use cases and explore how each MEC system integrates into the 5G network. We also provide measurements from trials of the use cases over a live GEO satellite system and indicate in each case the improvements that result from the use of satellite in the 5G network. Abstract : Outputs from the EU project SaT5G to produce an integrated satellite terrestrial network are presented. A 5G satellite connected and fully 3GPP Rel 15/16 test bed with a 5G RAN of small cells is described. Results of trials on 5G applications; cell backhaul, content delivery and multi linking via satellite and terrestrial are presented.